Effectiveness of a Community-Based Intervention Model in Increasing Neonatal Visit Coverage - Ginting Munthe, Novita Br; Machmud, Rizanda; Semiarty, Rima; Serudji, Joserizal; Bachtiar, Adang; Yani, Finny Fitry; Symond, Denas; Nelwati, Nelwati (Journal of Neonatal Surgery, 2025)
Background: Low neonatal visit coverage remains a challenge in improving newborn health. Community-based interventions using the Pondok Dalam approach may provide a solution to enhance awareness and access to neonatal healthcare services. Objective: This study aims to evaluate the effectiveness of the Pondok Dalam community-based intervention model in increasing neonatal visit coverage. Methods: This study employed a quasi-experimental design with a pretest-posttest approach without a control group to assess the effectiveness of the community-based intervention. The sample consisted of 60 mothers with neonates aged 0-28 days residing in the working areas of five public health centers (puskesmas) in Serdang Bedagai Regency. Data were collected using questionnaires before and after the intervention and analyzed using the Paired Samples t-Test. Results: The study results indicated a significant increase in knowledge scores (p < 0.001), attitudes (p < 0.001), cultural practices (p < 0.001), husband/family support (p < 0.001), and the quality of neonatal visit services (p < 0.001) following the Pondok Dalam-based intervention. Conclusion: The Pondok Dalam community-based intervention model has proven to be effective in increasing neonatal visit coverage. Wider implementation in primary healthcare services is necessary to enhance the quality of neonatal care.